Genetic Diversity Evaluation of MARDI’s Coconut (Cocos nucifera L.) Germplasm using Simple Sequence Repeats - Khairun, H. N.; Jaafar, Mohd Azwan; Shahril, A. R.; Sentoor, G. K.; Siti, N.; Fairuz, M. Y.; Habibuddin, H.; Norzihan, A. (International Coconut Community, 2016)
A total of 18 simple sequence repeat (SSR) markers have been optimized and used to genotype coconut (Cocos nucifera L.). These markers were used to genotype 23 coconut varieties that were maintained in MARDI’s germplasm collection. Fifteen SSR loci were polymorphic markers while the remaining three SSR were monomorphic. The number of alleles ranged from 2 to 19 with a mean number of 8.53 per locus. The expected heterozygosity values in each variety ranged from 0.07 to 0.61, with an average value of 0.52. Several varieties could be successfully differentiated by using these 15 SSR markers such as Cameroon Red Dwarf x West African Tall hybrid, Mawa hybrid, Malayan Tall x Cameroon Red Dwarf hybrid, Malayan Red Dwarf x Rotuman hybrid, Catigan, Pandan and Laguna. A UPGMA Dendogram showed Niu Damu as an outlying group with high dissimilarity from all other varieties. Analyses using the STRUCTURE software showed all 23 varieties to be clustered into 21 genotypic groups. This new information will greatly contribute towards characterization of the MARDI’s coconut germplasm collection and to develop a SSR tool for the identification of new coconut varieties in Malaysia.